Reconstructing the management of Islamic education learning technology: Synthesizing the TPACK framework with principles of Islamic leadership for sustainable innovation - Huda, Moh. Nurul (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
The rise of the digital period creates important pressures on Islamic Religious Education (IRE) institutions to embed educational technologies that elevate both relevance and productivity. Nevertheless, this process of integration frequently unfolds without a management framework that is congruent with the core values of Islam, resulting in a discord between technological advancements and the educational spiritual objectives. This research employs a meticulous examination of documents through library studies to address the current void. The principal contribution of this article is the proposal of an innovative conceptual framework that integrates the Technological Pedagogical Content Knowledge (TPACK) model with the essential tenets of Islamic management and leadership, specifically Amanah (trust and responsibility), Syura (consultation), 'Adl (justice), and Fathanah (wisdom). This integrated framework, designated as TPACK-Islami, not only directs the technical and pedagogical dimensions of technology incorporation but also roots them within an ethical and spiritual context. The analysis reveals that by contextualizing TPACK with regard to Amanah, guiding pedagogical methodologies through Syura, selecting technology through Fathanah, and ensuring just implementation via 'Adl, IRE institutions can steer technological advancements that are not only cognitively proficient but also fortify the character (akhlaq) development of learners. This article delineates specific managerial implications for leaders in Islamic education, particularly concerning strategic planning, professional development for educators, and program assessment, while also proposing avenues for future research to empirically validate the suggested framework.